Media Sosial Universitas Muhammadiyah Yogyakarta @UMYogya dalam Perspektif Social Big Data - Ayu Amalia (Jurnal Riset Komunikasi, 2021)
Social big data is the recently popular for big data management with a new approach that specifically refers to data generated from social media. Universitas Muhammadiyah Yogyakarta as a reputable higher education institution with social media accounts @UMYogya, is a potential contributor in the context of big data. This research is a descriptive study that aims to reveal the potential of social media @UMYogya quantitatively by using tools in the form of social media analytics features. Social media as a mid-tier influencer has an intense engagement with its social media viewers at a significant level, by implementing a social media management scheme that refers to the big social data diagram, social media @UMYogya as a representation of Universitas Muhammadiyah Yogyakarta potentially increasing the ‘impact’, involving stakeholders and developing social media by referring to the potential of social big data itself.